Respon Pemanfaatan Limbah Cair Kelapa Sawit Terhadap Pertumbuhan dan Produksi Tanaman Kailan (brassica oleraceae l.) - Tulus Nopranto Nainggolan; Gusmeizal Gusmeizal; Ellen L. Panggabean (Jurnal Ilmiah Pertanian ( JIPERTA), 2022)
The Response Of Liquid Waste Utilization Of Palm Oil On Growth And Production Plant Of Kailan (Brassica Oleraceae L.). Under the guidance of  Ir. Gusmeizal, MP as the commission chairman of counselor and Ir. Ellen L. Panggabean, MP as the commission member of counselor.  This research was conducted at the experimental garden of Agriculture Faculty University of Medan Area, located on Jl. PBSI Medan Estate. This research was conducted began in April 2016 until June 2016. The purpose of this research was to determine the response of liquid waste utilization of palm oil on growth and production plant of kailan. This research was conducted by using Randomized Block Design (RBD) non factorial which consists of 4 levels of treatment are: L0 = Control (NPK 20 g/plot),  L1 = 1 l/plot,  L2 = 2 l/plot,  L3 = 3 l/plot. Parameters observed were height of plants, leaf number, stem diameter, fresh weight of harvest by plot, fresh weight of harvest by sample, fresh weight of sell by plot, fresh weight of sell by sample. The results of research showed that utilization of liquid waste of palm oil did not show significantly different results in all parameters of observation, but the liquid fertilizer from palm oil waste is able to compensate for the growth and production plant of kailan (Brassica oleracea L.) that fertilized with NPK.